Mechanical properties of lanthanum zirconate-based composite thermal barrier coatings. (4th July 2019) - Zhang, Jing; Guo, Xingye; Zhang, Yi; Lu, Zhe; Choi, Hyun-Hee; Jung, Yeon-Gil; Kim, In-Soo
ABSTRACT: Lanthanum zirconate is a promising candidate material for thermal barrier coating (TBC) applications due to its low thermal conductivity and high temperature phase stability. However, its application is limited by thermal durability caused by low fracture toughness and low coefficient of thermal expansion. We recently developed LZ/8YSZ composite TBC systems using blended LZ and 8YSZ powders, which have demonstrated excellent thermal cycling performance. In this study, the mechanical properties of the composite TBCs were characterised using both nanoindentation and Vicker's microhardness tests. The nanoindentation results show that both Young's modulus and nanohardness increase with increasing 8YSZ content, suggesting the mechanical properties can be tailored by changing the volume ratio of 8YSZ. The ratios of Young's modulus to nanohardness remain constant, ∼18, irrespective to the coating's composition. The microhardness results show the same dependence with 8YSZ content, which is confirmed by the analytic models based on composite theory.